Adaptive myopia. Part 3. Interaction of physiological mechanisms of eye’s focusing with mechanisms of acquired myopia development (Ukrainian Journal of Ophthalmology, 2026)
Adaptive myopia. Part 3. Interaction of physiological mechanisms of eye’s focusing with mechanisms of acquired myopia development